Amplified sensitization of Er3+ luminescence in silica by AuN quantum clusters upon annealing in a reducing atmosphere. Issue 101 (18th October 2016) - Cesca, Tiziana; Kalinic, Boris; Maurizio, Chiara; Michieli, Niccolò; Scian, Carlo; Mattei, Giovanni
Abstract : Au N quantum cluster sensitization of Er 3+ photoemission in silica is boosted by H passivation of Si dangling bonds around the clusters. Abstract : Finding effective strategies for improving the luminescence emission performance of Er 3+ ions in silica is of paramount importance for the realization of efficient Er-based nanophotonic devices. To this aim, in the present work the sensitization mechanism of room temperature Er 3+ luminescence by Au N quantum clusters, upon annealing in a reducing atmosphere, was investigated by photoluminescence characterization of Er–Au co-implanted samples in which Au ions were implanted at a low fluence of 3.4 × 10 14 Au + per cm 2 . The role of the annealing atmosphere was unveiled by comparing the emission properties of samples thermally treated in reducing and inert atmospheres. A significant amplification of the Er 3+ sensitization efficiency (up to a 6× enhancement of the photoluminescent intensity) was revealed upon annealing in a reducing atmosphere and the possibility to get efficient room temperature Er 3+ luminescence from Er–Au co-implanted samples with only a limited amount of sensitizing agents was demonstrated and discussed.